Comparison of different methods for evaluating the relationship between facial nerve and benign parotid tumors. (October 2022) - Kojima, Takashi; Matsumoto, Fumihiko; Suzuki, Yo; Sakyo, Airi; Kojima, Masataka; Fujimaki, Mitsuhisa; Ohba, Shinichi
Objectives: The goals of benign parotid gland tumor resection are complete resection of the lesion and preservation of the facial nerve function. As the facial nerve cannot be directly visualized via imaging modalities, several methods, including the facial nerve line, Utrecht line, retromandibular vein, Stenon duct, and minimum fascia-tumor distance techniques, have been developed to estimate its location. However, there are no reports on their accuracy in determining tumor location. In the present study, we aimed to assess the diagnostic accuracy of these methods based on tumor location. Methods: This retrospective study analyzed medical records and histological reports of 359 patients with various types of benign parotid gland tumors who underwent a parotidectomy between April 2014 and March 2020. The tumor location was subdivided into the following sections: anterior, superior, inferior, and middle. The tumor location was estimated using five methods: facial nerve line, Utrecht line, retromandibular vein, Stenon duct, and minimum fascia-tumor distance. The final diagnosis of superficial or deep lobe tumor was made based on surgical findings. Results: Each method showed a higher accuracy for superficial tumors (was more than 90%) than for deep lobe tumors. In contrast, for deep lobe tumors, the accuracy of diagnosis with the facial nerve line, Utrecht line, and retromandibular vein methods was low, in the 30% range. Among all methods, the Stenon duct method had the highest accuracy in the diagnosis of deep lobe tumors. The SD method was most useful in cases where both the duct and tumors were detected. The minimum fascia-tumor distance method had the second highest diagnostic accuracy (63%); however, for anterior tumors, it tended to provide false negatives. Conclusions: All tested methods were useful in diagnosing superficial lobe tumors; however, they were not helpful in diagnosing deep lobe tumors, especially anterior tumors.